Analysis of Factors Affecting the Earnings Management on the Consumer Goods Industry Issuers on the IDX - Yuni Triliawati (Journal of Contemporary Information Technology, Management, and Accounting, 2020)
This study aims to analyze and test the effect of factors in diamond fraud theory on earning management actions in the issuers of the consumer goods industry sector. These factors consist of pressure (financial stability, leverage, personal financial need, financial targets), opportunity (nature of industry, ineffective monitoring), rationalization, capability. The sampling technique in the study used purposive sampling. The research sample is 80 financial data from 20 listed companies during the 2015-2018 period based on established criteria. Data analysis methods in this study used descriptive statistics, data quality tests, classic assumption tests, and hypothesis testing which consisted of multiple linear regression analysis methods, coefficient of determination test, F test, and t test. The results showed that leverage and financial targets affect the earning management actions, while financial stability, personal financial needs, nature of industry, ineffective monitoring, rationalization, and capability do not affect earning management.